SUGGESTIONS BY HOME-BASED CAREGIVERS CARING FOR PEOPLE LIVING WITH HIV AND AIDS ON HOW SOCIAL WORKERS COULD SUPPORT THEM IN MANAGING THEIR WORK-RELATED CHALLENGES - Lekganyane, Maditobane Robert; Alpaslan, Nicky (Social Work/Maatskaplike Werk, 2019)
A lacuna in the indigenous social work literature on how home-based caregivers caring for people living with HIV and AIDS (PLWHA) would like to be supported by social workers in their caregiving duties led to the launching of a qualitative investigation. This investigation was conducted in South Africa to look into (i) the challenges experienced by caregivers in exercising their duties of caring for PLWHA, (ii) how they manage such challenges, and (iii) suggestions on how social workers can support them. This article presents findings specifically pertaining to suggestions made by the caregivers on how social workers can support them.